Risk Prediction After Myocardial Infarction by Cyclic Variation of Heart Rate, a Surrogate of Sleep-Disordered Breathing Assessed From Holter ECGs - Cao, Xu; Müller, Alexander; Dirschinger, Ralf J.; Dommasch, Michael; Steger, Alexander; Barthel, Petra; Laugwitz, Karl-Ludwig; Schmidt, Georg; Sinnecker, Daniel (Frontiers in Physiology, 2020)
Aims: Sleep-disordered breathing (SDB) is common among cardiac patients, but its role as an independent risk predictor after myocardial infarction (MI) is unclear. SDB causes cyclic variation of heart rate (CVHR). The aim of this study was to score Holter ECGs of a large cohort of MI survivors for SDB-related CVHR to investigate its value for mortality prediction. Methods: 1590 survivors of acute MI in sinus rhythm were prospectively enrolled and followed for 5-year all-cause mortality. Heart rate (HR) tachograms were generated from nocturnal (00:00-06.00 am) segments of Holter ECGs, and the minutes with CVHR were quantified by a previously-described and validated algorithm. According to a pre-specified cutpoint, SDB was assumed if CVHR was present during ≥72 minutes. Results: 77 patients (4.8%) had flat HR tachograms which prohibited analysis for SDB. Of the remaining 1513 patients, 584 (38.6%) were classified as having SDB. Mortality rates in groups stratified according to ECG-derived SDB did not differ significantly. Taken as a continuous variable, low CVHR duration was associated with increased mortality. The mortality of patients with flat HR tachograms was significantly increased, even after adjustment for age, sex, LVEF, GRACE score and diabetes mellitus. Mortality prediction by a flat HR tachogram was also independent of heart rate variability, heart rate turbulence, and deceleration capacity. Conclusion: In Holter ECG recordings of survivors of acute MI, signs suggestive of SDB were frequently present, but not associated with mortality. A flat nocturnal HR tachogram was a strong, independent predictor of 5-year all-cause mortality.